Presurgical Obturator for an Infant with Cleft Lip and Palate in Pranangklao Hospital: a Case Report - Plengsringam, Nuchanart (Journal of Health Science of Thailand, 2017)
Neonate with cleft lip and palate has problems in feeding, deformity of nasal and maxillary struc-ture. Obturator is an appliance that is used to restore the separation between oral and nasal cavities inorder to solve these problems and simplify lip and nose plastic surgical procedures. This article reports a case of a 11-day-old girl with left unilateral complete cleft lip and palate being treated in Pranangklao Hospital, Nonthaburi, with Chiang Mai University - Nasoalveolar Molding I (CMU-NAM I) passive and active obturators for 79 days prior to a surgical repare of lip and nose. The treatment outcome was highly satisfactory. Patient has good sucking; the cleft width was reduced; and the nose shape was improved.